Effect of salting and ripening on the physicochemical and sensory quality of goat and sheep cured legs. (December 2017) - Teixeira, Alfredo; Fernandes, Aline; Pereira, Etelvina; Manuel, Aristides; Rodrigues, Sandra
Abstract: Physicochemical and sensory characteristics of sheep and goat cured legs were evaluated. The pH values (5.7–5.8) and aw (0.87 and 0.83) found to be adequate to control meat deterioration, promoting safety and stability to shelf life of products with respect to microbial growth. The high protein (46.2 and 38.4%) and low fat (5.3 and 8.7%) percentages of the goat and sheep cured legs were the main evidence of the effect of salting and ripening processes. A low cholesterol content of 4.5% is particularly evident in sheep cured legs. Curing process produced a slight increase in the P/S ratio 0.23 and 0.17 for goat and sheep cured legs, respectively. TBARS values are much lower than the value of 2 mg of MDA/Kg which is the upper limit of rancidity. Physico-chemical and sensory characteristics indicate that producing cured goat and sheep legs from cull animals can be an interesting way of adding value to animals with very low commercial prices. Highlights: Contribution to give added value to meats with very low commercial value Describe the physicochemical and sensory characteristics of sheep and goat cured legs. The high protein and low fat contents make the goat and sheep cured legs an interesting and nutritionally balanced product.